Assessing the Effectiveness of Teacher and Educational Staff Training Programs on Student Competency Development - Try Susanti; Rizki; Agil Rahmadani; Irfan Pratama; Yeye Muhamad Arif (Journal of Educational Management Research, 2026)
This study aimed to evaluate the effectiveness of training programs for teachers and educational staff in enhancing students’ competencies. A qualitative research approach was employed, with data collected through observations, interviews, and document analysis. The study involved educational personnel and school administrators who participated in professional development activities. The findings indicate that continuous training programs contribute positively to improving instructional quality through the adoption of innovative teaching strategies, digital technologies, and artificial intelligence (AI)-based learning applications. Enhanced teacher competencies were found to have a direct impact on students’ learning experiences and competency development. However, the effectiveness of the programs remains constrained by limited technological infrastructure, restricted access to online training opportunities, and insufficient financial support. Participants also highlighted the importance of face-to-face training formats in fostering deeper interaction, engagement, and understanding. The study implies that sustainable professional development initiatives require adequate institutional support, improved technological facilities, and well-structured training programs to maximize their long-term impact on educational quality and student competency enhancement.